2010
DOI: 10.1682/jrrd.2009.12.0204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bracing on dynamic patellofemoral contact mechanics

Abstract: Abstract-Decreases in patellofemoral pain have been demonstrated with bracing; however, the mechanisms of pain reduction remain unclear. Our purpose was to evaluate the hypothesis that patellofemoral bracing decreases peak pressure on the retropatellar surface through an increase in patellofemoral contact area. Nine cadaveric knees were tested during simulated freespeed walking with no brace, a knee sleeve, two different patellar stabilization sleeves, and a wrap-style patellar stabilization brace. Contact are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…It has previously been reported that patients with patellofemoral pain display altered or compensatory movement patterns when descending from a step [13,14,16,29,30]. This phenomenon was also observed in this study, manifested by an increased amount of medial/lateral displacement or 'wobble' of the knee and in some cases, of the trunk and upper limbs.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It has previously been reported that patients with patellofemoral pain display altered or compensatory movement patterns when descending from a step [13,14,16,29,30]. This phenomenon was also observed in this study, manifested by an increased amount of medial/lateral displacement or 'wobble' of the knee and in some cases, of the trunk and upper limbs.…”
Section: Discussionsupporting
confidence: 86%
“…It is therefore possible that this contributed to the mechanical stability of the patella as it tracked in the femoral trochlear groove during the step descent. Patella sleeve braces, of the type used in this study, have been shown to cause the patella to engage in the trochlear groove earlier during flexion through their compressive mechanism on the quadriceps tendon [29]. This could also have contributed to the improved stability observed in this study.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…If the response is positive from patellar taping, it may also be positive with a lateral buttress knee brace. Sleeve braces have been shown to help with patella tracking while wrap-style braces reduce peak patellofemoral pressure by changing the location of contact and pressure [35]. However, a recent randomized trial evaluating the use of bracing for patellofemoral pain associated with arthritis found no clinical benefit for bracing [36].…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…Patellar bracing provides certain advantages over taping, including longer equipment life due to reusable materials, and lack of possible allergic dermatitis to adhesives. As bracing provides similar biomechanical effects as taping, such as increasing joint contact area [9], it should similarly reduce symptoms, but the results thus far have been more conclusive for the use of bracing in patellar instability, and less convincing for PF OA [6, 10]. …”
Section: Introductionmentioning
confidence: 99%